Roughness and its effects on flexural strength of dental yttria-stabilized zirconia ceramics - Amarante, José Eduardo Vasconcellos; Pereira, Marcos Venícius Soares; de Souza, Grace Mendonça; Pais Alves, Manuel Fellipe R.; Simba, Bruno Galvão [UNESP]; dos Santos, Claudinei (Elsevier, 2019)
This study evaluated the effect of the surface roughness parameters on the flexural strength of Yttria-partially stabilized zirconia, Y-TZP ceramics: ZrO2 (3 mol%) or ZrO2 (5 mol%), as function of different surface finishing protocols: polishing or alumina (Al2O3) blasting. Zirconia discs were manufactured by CAD/CAM prototyping and sintered at different temperatures. The specimens were characterized by X-ray diffraction, scanning electron microscopy, biaxial flexural strength test and 3D profilometry. In all specimens tetragonal Y2O3-ZrO2 was observed to be the main crystalline phase. The 3D profilometry indicated that alumina blasting of ZrO2 (3 mol%) increased the roughness Ra around 16–26 times as opposed to the polished surfaces, and approximately 38 times for ZrO2 (5 mol%) specimens when compared to the polished samples. The results of flexural strength indicate that groups of ZrO2 (3 mol% Y2O3) ceramics present a reduction of 21–23% from polished to alumina blasted specimens. In the group of ZrO2 (5 mol% Y2O3) ceramics, a flexural strength reduction of 37.5% was observed. A correlation between flexural strength, failure size and different roughness parameters: Ra (arithmetic average of the absolute values of the profile heights over the evaluation length), Rz (measure of the ordinates of the five highest peaks and the five deepest valleys along the specimen's length) and PV (mean values of peak and valley measured in the specimen space) is proposed and indicates that Rz and PV should not be neglected in a systematic evaluation of the surface roughness effect on the bulk mechanical properties of dental ceramics.
Keywords: Dental materials; Flexural strength; Roughness parameters; Zirconia